2021
DOI: 10.1177/2167702621993867
|View full text |Cite
|
Sign up to set email alerts
|

Inflexible Interpretations of Ambiguous Social Situations: A Novel Predictor of Suicidal Ideation and the Beliefs That Inspire It

Abstract: Suicidal ideation has been linked to a bias toward interpreting ambiguous information in consistently less positive or more negative manners ( positive/negative interpretation bias), implying that information-processing biases might distort beliefs thought to inspire suicidal ideation (e.g., those regarding burdensomeness). Therefore, in the present study, we examined whether suicidal ideation and beliefs highlighted in theories of suicide are related to positive/negative interpretation bias and/or a bias agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 114 publications
(160 reference statements)
3
13
0
Order By: Relevance
“…When combined with the feature looking for positive sides, positive reappraisal features were more important than features of repetitive negative thinking to predict concurrent and prospective suicidal ideation. This observation is consistent with recent longitudinal research indicating that interpretation processes predict increases in suicidal ideation (Everaert et al, 2021). This finding warrants further research exploring the etiological significance of the pathways from reappraisal or reinterpretation to suicidal ideation.…”
Section: Discussionsupporting
confidence: 92%
“…When combined with the feature looking for positive sides, positive reappraisal features were more important than features of repetitive negative thinking to predict concurrent and prospective suicidal ideation. This observation is consistent with recent longitudinal research indicating that interpretation processes predict increases in suicidal ideation (Everaert et al, 2021). This finding warrants further research exploring the etiological significance of the pathways from reappraisal or reinterpretation to suicidal ideation.…”
Section: Discussionsupporting
confidence: 92%
“…The IIT also eliminates the confound of varying reading comprehension levels across different developmental stages, making it preferable for developmental studies examining whether inflexible or biased interpretations precede and predict psychopathologies. For example, the IIT could be used to investigate the temporal priority of inflexibility over suicide ideation, which was linked to interpretation inflexibility in a recent, longitudinal study of adults (Everaert et al, 2021). The IIT is also preferable for research using electroencephalographic or functional magnetic resonance imaging to uncover biobehavioral markers of interpretation bias and inflexibility, as picture-based stimuli may afford more precise stimulus timing.…”
Section: Discussionmentioning
confidence: 99%
“…Emotional BADE task metrics were calculated based on the scoring method employed in prior work (Everaert et al, 2021). Negative and positive interpretation flexibility indices were calculated respectively to represent the ability to revise negative and positive existing beliefs in light of disconfirming evidence.…”
Section: Data Reduction and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Starting with Beck's influential cognitive model of depression (Beck et al, 1979), numerous studies have provided evidence for the presence of dysfunctional cognitions in people with depressive symptoms (Czyz et al, 2016; Everaert et al, 2021; Perez & Rohan, 2021). Besides other types of cognitions, a cumulative body of research has suggested that depression is particularly characterized by dysfunctional expectations (Kube et al, 2020).…”
Section: Introductionmentioning
confidence: 99%